ASSESSEMENT OF PURIFIED COLLAGENASE INHIBITION ACTIVITY FROM STAPHYLLOCOCCUS AUREUS HN77 BY SOME LOCAL PLANTS EXTRACT - Salih, Hanaa. N.; Hussein, S. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to inhibition of purified collagenase produced from S. aureus by local plants inhibitors (fruits and leaves). Sixty two local isolates of S. aureus which were isolated and identified by biochemical test subjected to the primary and secondary screening processes to select the active S. aureus isolate for collagenase production. Among these isolates, forty nine isolates with maximum zone of hydrolysis ability in primary screening (the ratio of Z/G more than 10 mm) were selected for secondary screening. It has been found that S. aureus HN77 had the highest productivity of the enzyme (49.122 U/mg protein). The selected isolate with highest level of collagenase activity was identified as S. aureus HN77 according to vitek test. The optimum conditions of collagenase production by selected isolate using submerged fermentation were obtained with medium (D) contain collagen as the best production medium, 2% starch as the best carbon source, 2% yeast extract/peptone as nitrogen source, temperature 37 °C and pH 7, after 48 hr. of incubation period, the specific activity was reached to1502.15 U/mg. The enzyme was purified by gel filtration chromatography using Sephadex G-150 then concentration by sucrose. The results shown an increase in final purification folds 6.1 time with an enzyme yield of 85.2%.The purified enzyme was exhibited maximal activity and stability at pH 7.0. The optimal temperature for purified enzyme activity was 45°C and it was stable until 45°C.The highest rate of enzyme specificity found with collagen. Collagenase was inhibited with local plants extract (fruit and leaves). Fruit of black fig extract inhibit 90% of collagenase activity while the inhibition efficiency of collagenase with grape leaf was reached to 12%.